Analisis Kelayakan Penyajian Buku Teks Bahasa Indonesia Kelas XII Kurikulum 2013 Terbitan Kemendikbud 2018 - Adristi Afdal; Afiyah Masruri; Ajeng Nabilla Anugrah; Amay Lanjar Wulandari; Andini Fitria; Muhammad Mukhlis (UIR Press, 2022)
Textbooks are one of the most important teaching materials in the learning-learning process, especially for teachers who are still lacking in making their own teaching materials. Standard textbooks have aspects including content, language, presentation and graphics. The presentation of textbooks is one of the four criteria for the eligibility of textbooks. A good presentation of textbooks will also have a good impact on learning. The feasibility of the presentation in this study includes three stages, namely: presentation techniques, presentation support, and coherence and coherence in the flow of thought. The purpose of this study is to describe and explain the feasibility analysis of presenting Indonesian language textbooks for class XII 2013 curriculum published by the Ministry of Education and Culture 2018. This book is used by high school students.